Increasing and decreasing faith and its relationship to human work Research in Islamic Thought and Creed - Owaid Thahab, Dheyaa (Journal of College of Education, 2022)
The research aims to clarify the relationship between faith and human action, through the noble Qur’anic verses, the noble Prophetic hadiths, the hadiths of the Ahl al-Bayt, the Companions and the followers, and the statement of actions that increase faith, and actions that detract from and contradict faith. The research was divided into an introduction and two sections. The first topic was about the relationship between faith and human action in the Holy Qur’an, and what are the actions that accompany faith, and what are the actions that contradict faith, through the Qur’anic verses. The second topic was about the relationship of faith with human action through the honorable prophetic hadiths, and what actions accompany faith, and what actions contradict it. The conclusion included the results of the research and recommendations. The researcher recommended that educational, educational and religious institutions bear the responsibility of consolidating the principles of faith and supreme values in the souls of society, in order to rise to the lofty ranks that preserve human dignity, and the results of which would be that the good prevails in all of society and live in peace and security.